Cytomegalovirus colitis followed by ischemic colitis in a non-immunocompromised adult: A case report - Hasegawa, Tsuyoshi (World J Gastroenterol, 2015)
We report a rare case of cytomegalovirus (CMV) colitis followed by severe ischemic colitis in a non-immunocompromised patient. An 86-year-old woman was admitted after experiencing episodes of vomiting and diarrhea. The next day, hematochezia was detected without abdominal pain. The initial diagnosis of ischemic colitis was based on colonoscopy and histological findings. The follow-up colonoscopy revealed a prolonged colitis. Immunohistochemical staining detected CMV-positive cells following conservative therapy. Intravenous ganciclovir therapy led to successful healing of ulcers and disappearance of CMV-positive cells. The prevalence of CMV infection is common in adults. CMV colitis is relatively common in immunocompromised patients; however, it is rare in immunocompetent patients. In our case, CMV infection was allowed to be established due to the disruption of the colonic mucosa by the prior severe ischemic colitis. Our experience suggests that biopsies may be necessary to detect CMV and the prompt management of CMV colitis should be instituted when intractable ischemic colitis is observed.